Use of urine alarms in toilet training children with intellectual and developmental disabilities: A review. (June 2016) - Levato, Lynne E.; Aponte, Courtney A.; Wilkins, Jonathan; Travis, Rebekah; Aiello, Rachel; Zanibbi, Katherine; Loring, Whitney A.; Butter, Eric; Smith, Tristram; Mruzek, Daniel W.
Highlights: Urine alarms represent technology that could facilitate toilet training. A literature review was conducted on urine alarms in children with IDD. The review yielded 12 articles that were evaluated by specified research criteria. Interventions that include urine alarms should be considered experimental. More high quality research is needed. Abstract: The purpose of this review is to describe and evaluate the existing research on the use of urine alarms in the daytime toilet training of children with intellectual and developmental disabilities (IDD). A systematic literature search yielded 12 studies, many of which were published over a decade ago. The findings suggest that interventions that incorporate the use of urine alarms are promising in the treatment of daytime enuresis for children with IDD; however, more carefully controlled research is needed to confirm these findings and elucidate the precise role urine alarms may play in toileting interventions. Methodological strengths and limitations of the body of research are discussed.